Culturally sensitive approaches to internet addiction among adolescent and young adult: the integration of Islamic practices - Abdul Razak, Afidatul Hanim; Tengku Kamarulbahri, Tengku Mohd Saifuddin (GLOBAL ACADEMIC EXCELLENCE (M) SDN BHD, 2024)
Internet addiction is increasingly recognized as a significant mental health concern, and is now included in DSM-5 TR as internet gaming disorder. Cybersexual addiction, a subtype of internet addiction, presents unique treatment challenges due to the pervasive need for online activities. This paper examines the incorporation of Islamic principles in the treatment of internet addiction among Muslim patients. The aim is to explore culturally sensitive approaches that align with Islamic practices to effectively address internet addiction. To highlight the specific challenges and benefits of integrating Islamic principles in managing internet addiction, a review of various databases was conducted. Key search terms included "internet addiction," "Islamic principles," "religious therapy," and "psychospiritual treatment." A detailed case vignette was included to demonstrate the practical application of integrating Islamic principles in treatment, highlighting the psychospiritual aspects and their impact on patients' emotional well-being. This paper discusses the principles of treatment, patient suitability, therapist preparedness, and potential limitations. Integrating religious principles as part of a psychospiritual approach shows promise in behaviour therapy for Muslim individuals suffering from internet addiction.